Positioning and vibration control of a flexible structure in slewing motion by applying Shape Memory Alloys - Janzen, Frederic Conrad [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Flexible structures with slewing motion has been found with increasing frequency in various types of applications, because they are more efficient than their rigid competitors. The study of these systems is important because of the vibrations coming from the mass reduction of structures. Many works have been published presenting control techniques applied in reducing the effects of these vibrations. Several studies demonstrate the application of intelligent materials as actuators for this application. This paper presents a proposal for controlling the angular positioning and vibration of a flexible structure in slewing motion. For such compounds an intelligent actuator materials known as Shape Memory Alloy is employed to control the vibration of the flexible structure. To control the system, the control technique known as State Dependent Ricatti Equation (SDRE), is applied to the control. In order to analyse the dynamics of the system with the proposed control the mathematical modelling of the system is considered and its validation by developed an experimental prototype. Numerical simulations are carried out to analyse the viability of the control and experimental tests are performed in order to validate the theoretical model and the proposed control.

Estruturas flexíveis com movimento de rastreamento tem sido encontradas com frequência cada vez maior em diversos tipos de aplicações, por serem mais eficientes do que suas concorrentes rígidas. O estudo desses sistemas é importante por conta das vibrações advindas da redução de massa das estruturas. Muitos trabalhos têm sido publicados apresentado técnicas de controle aplicadas na redução dos efeitos dessas vibrações. Vários trabalhos demonstram a aplicação de materiais inteligentes como atuadores para esse tipo de aplicação. Sendo assim, o presente trabalho apresenta uma proposta para o controle do posicionamento angular e da vibração de uma estrutura flexível em movimento de rastreamento. Para tal, atuadores compostos de um material inteligente conhecido como Liga com Memoria de Forma são empregados para o controle da vibração da estrutura flexível. Com relação ao controle, a técnica de controle conhecida como Equações de Ricatti Dependentes dos Estados (SDRE) é aplicada para o controle. Com o objetivo de analisar a dinâmica do sistema com o controle proposto considera-se a modelagem matemática do sistema e sua validação através do desenvolvido de um protótipo experimental. Simulações numéricas são realizadas para analisar a viabilidade do controle proposto e testes experimentais são realizados com a finalidade de validar o modelo teórico e a proposta de controle.
Controle do posicionamento e vibração de uma estrutura flexível em movimento de rastreamento com aplicação de ligas com memória de forma
Keywords: Slewing; Flexible beam; Active control; Shape Memory Alloys